Hubungan Intensitas Penggunaan Media Sosial Dengan Kualitas Tidur Pada Remaja - Maulinda, Nandha Dela; Priasmoro, Dian Pitaloka; Fani, Rifa'tul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: This research aims to determine the relationship between the intensity of social media use and sleep quality among teenagers. Methods: This research uses a quantitative research design with a cross sectional approach. The population of this study was all teenagers from SMAN 1 Gondanglegi, totaling 347 teenagers with a sample of 186 teenagers. The technique used is stratified random sampling. The research was conducted from November 21, 2024 to November 28, 2024. The research instrument used the Internet Addiction Test (IAT) questionnaire and the Pittsburg Sleep Quality Index (PSQI) questionnaire. Bivariate analysis results using Spearman rank. Results: The Results were tested using Spearman rank. The obtained sig (2-tailed) p value = 0.001 < 0.05 shows that there is a significant relationship between the intensity of social media use and the sleep quality of teenagers at SMAN 1 Gondanglegi. The research results have a correlation coefficient (r) of 0.871, including research with a strong relationship strength and positive direction, which means that the higher the intensity of social media use, the worse the sleep quality of teenagers. Conclusion: Based on the results of the research, it shows that the intensity of social media use is related to sleep quality. It is hoped that this can increase knowledge about the impacts caused if the intensity of social media use is too high and respondents can find out how to maintain better sleep quality.